Pemanfaatan logam mulia sebagai elemen estetis pada jam tangan berbahan kayu Ulin - Royke Vincentius Febriyana; Ramadhan S Pernyata (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2023)
The Indonesian government is seriously developing products made from endemic natural resources. One of the potential materials to be further developed is wood. The endangered Eusideroxylon Zwageri, commonly known in Indonesia as Ulin Wood, are an endangered flora species that is difficult to find outside the South-East Asia Region. The wood is commonly used for construction and building materials, causing massive exploitation and deforestation. The research initiated a new approach to making smaller products yet having higher economic values. By adding precious metals as the aesthetical elements, it is wished that the product could be classified as precious/semi-precious jewellery, thus elevating its economic value. The research employing method developed by Paul Harris involves the Define, Research, Ideate, Prototype, Select, Implement, and Learn stages. The CNC 3-axis Milling machine will be used to make the prototype. The results are a Wrist watch design with precious metal aesthetical elements. The prototypes are made considering technical boundaries, as the journal explains.